WRITERS AND THEIR WAYS WITH WORDS: MIGRATION AND LANGUAGE IN CONTEMPORARY GERMANY - Adelheid R. Eubanks (European Scientific Journal, ESJ, 2014)
On 9 and 10 December 1991, the European Citizen was created during the Maastricht European Council. Since then, Europeans of the member states of the European Union (EU) have witnessed the introduction of a common currency, and the institutional, administrative, and civic Europeanization of Europe characterizes an arguably new Europe for the new millennium. In contrast to the administrative and civic Europeanization, there many and varied debates about what it means or may mean to be European and about European culture. In the context of these discussions, the comparative study of literature of migrants can be productive. Although somewhat different for the individual EU member states, the history of literature of migrants and its reception have unfolded in similar ways. In addition to the creation of a conflicted relationship between national and migrant literature, terms like the German Gastarbeiterliteratur have not only created a separate and distinct category for migrant literature, but have also served to limit its authors to a single characteristic (they are ‘guest workers’) and, by extension, the content of the works to a few themes such as feelings of loneliness, loss of home, a sense of isolation, etc. Significantly, what dominated the discourse about migrant literature was the concern with themes rather than with its vehicle, i.e., language. The literary productions of migrants to Germany during the past two decades invite comparison of these works to explore the extent and degree to which they are contributions to the debates about ‘European identity’. As basis for comparison serve examples from diverse texts and authors with diverse language backgrounds such as Italian, French, Japanese, Arabic, and Turkish, for example. The authors are different in terms of both their (or their parents’) countries of origin and in terms of their current homes and languages. The intentional reference to such variegated works serves to illuminate that despite the authors being subject to different first languages, they also have in common the translinguistic character of their texts. Importantly, the translinguistic aspects of the texts do not constitute the encounter (or even clash) between two given cultures (homeland and country of residence). Instead, each of the texts presents instances of the linguistic and creative potential when any two cultures ‘meet’ to inform each other and, in the process, both emerge as changed. One of the effects on the reader/recipient of the text or texts is defamiliarization with his or her native language; she or he is thus invited not only to encounter something (another culture/country) or someone (the narrator) Other but to also experience the assumed ‘normal’ (most readers’ native language) as Other. In this sense, the different texts all ‘teach’ that alterity is not far away, but that it exists where one might not expect it (at home, in one’s native language). The creative, aesthetic and profound play with language may not bring anyone closer to answering questions about ‘European identity’ (and may indeed raise new questions in addition to existing ones). However, the turn to its constitutive medium, i.e., language, clearly outlines the challenges that are implicit in recent migrant literatures across Europe and across other parts of the world. For Germany (and Europe), one of these challenges is to acknowledge current realities (as a consequence of historical phenomena) and to reimagine itself as the heterogenous space it has always been.